Malawi stories of change in nutrition: Overview - Harris, Jody; Chalemera, Jacqueline; Nowa, Mphatso; Saha, Devanik; Mhango, Brian; Lupafaya, Phindile; Museka Saidi, Tendai; Northcote, Callum; Bhaiji, Rashida; Roschnik, Natalie (Institute of Development Studies, 2022)
Malawi has made significant progress in improving nutrition outcomes in the past decades. Despite this, the rates of stunting and anaemia remain high and overweight and obesity amongst women is rising. Malawi remains one of the most committed countries to nutrition, ranking 3rd out of 45 African countries on the Hunger and Nutrition Commitment Index, but effective implementation of policies is still challenging. Progress is being inhibited by a lack of dedicated budget lines for nutrition at district level, over reliance on external donors, poor coordination and competing priorities for limited resources within sectoral budgets. The pandemic, climate change and the Ukraine war have disrupted food systems, increased prices of fuel, fertilizer, and food, and caused loss of harvest and livelihoods, threatening to reverse decades of progress. Positive and coordinated action is needed to increase financial commitment to food and nutrition security, ensure nutrition is prioritised in the nation’s economic and development agenda, and continue Malawi’s progress to reducing malnutrition.